PERLINDUNGAN TERHADAP KONSUMEN YANG TIDAK MENDAPATKAN SERTIFIKAT HAK MILIK SATUAN RUMAH SUSUN - Galih Husain Fauzi; Ermanto Fahamsyah (Fakultas Hukum Universitas Tarumanagara, 2018)
Indonesia is one of the countries that has large population. Development of public housing is tended in order that every family can occupy a public housing that is proper in healthful, secure, harmonious, and uniformed environment. The proper public house is a house construction that is fulfill safety regulation in its construction, suffice the minimum construction area, and give health for public house occupant. Realize of the statements, is needed for developing a construction public housing that can be occupied together in a public house building,that is devided in some parts separately, on vertical ar horizontal for every occupation. There is a lot of participants that is involved in developing a public house building, that is the developer as a participant for developing a public house building, owner, and the occupant as an organizer. The public house building certificate will be proven with a freehold public house building certificate for every occupant that is already fulfill the regulations as an owner in the public house building. Researcher has taken one of the case studies about the restraining of a freehold of public house building, with purpose of the case study is knowing a consumer protection legally toward the participant developer that is restraing a freehold public house building. Researcher solved this case study using the normative method that is supported an interview with related parties. Based on the research will be knowing that the regulation of a freehold public house building certificate does not applied clearly on the sanction of participant developer that is restraining a freehold public house building certificate on the time that is determined.